Basic science for aerospace vehicles. - McKINLEY, James L. (McGraw-Hill, 1963)
TABLA DE CONTENIDO: 1 Science fundamentals. 2 Elements of serodynamics. 3 Airfoils. 4 Aircraft in flight. 5 Blueprint reading. 6 Fundamentals of drafting. 7 Standards, materials, and hardware. 8 Structures for aerospace vehicles. 9 Hydraulics and pneumatics. 10 Plumbing for aerospace vehicles. 11 Weight and balance. 12 Pressure instruments. 13 Mechanical instruments. 14 Gyro instruments. 15 A look into outer space